Evaluation of Erosion Rate on Several Slopes on Ultisol Land With Peanut Plant on Small Plot Method and USLE Prediction in The Siborongborong District, North Tapanuli - Agri Dayanti Sipayung; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2013)
Cultivation of crops on sloping land is vulnerable to erosion if no soil and water conservation measures applied. This study was aim to quantify the erosion, determining the tolerable rate of erosion, and the erosion rate (TBE) in the Ultisol soil on slopes: 9%, 19%, and 32% plantedwith peanuts, using small plots and USLE predictions on July-October 2012 in the District Siborongborong. The results showed that the amount of erosion that occurs for USLE prediction method based on 12 years of rainfall data for the slopes of 9%, 19%, 32%, were 20.91, 69.43, and 166.47 tons/ha.year respectively, with moderate to very high TBE category. USLE prediction method based on rainfall data for four months of study with 9%, 19%, 32% slopes, were 0.4, 1.2,and 2.9 ton/ha.year respectively with low TBE category. Small methods plots for slopes of 9% 19%, 32%, were 12.36, 12.54, and 0.63 tons/ha year respectively with low TBE category. The magnitude of the tolerable rate of erosion at 17:17 tonnes/ha.year (17.17 mm/ha.year). Key words: Erosion, Ultisol land, Peanut Plant, Siborongborong